MERAJUT “KAMPUNG HARAPAN”: PENDEKATAN BUDAYA DAN PARTISIPATORIS DALAM RESOLUSI KONFLIK LATEN DI KAWASAN TRANSMIGRASI TELUK WONDAMA, PAPUA BARAT - Nurrahmi, Iflah Hayati; Vermanda, Diva; Fasya, Muhammad Ilham; Subarkah, Mohammad Gama; Fachruliansyah, Iman (Bhakti: Jurnal Pengabdian Masyarakat, 2026)
The Werianggi-Werabur Transmigration Area in Teluk Wondama, West Papua, faces challenges of social integration in the form of latent conflict between Indigenous Papuans (OAP) and transmigrants. This tension is manifested in residential segregation and recurring disputes regarding crop damage caused by livestock ("cattle vs. garden"). This community engagement activity aims to initiate culture-based conflict resolution through the "Damai Kita, Sejahtera Kita" Participatory Workshop. We used Participatory Action Research (PAR) as method. The pre-implementation phase utilized Social Network Analysis (SNA) to map key actors, as mediators, followed by social intervention through Focus Group Discussions (FGD) using Problem Tree and Conceptual Model tools. The results show three main achievements: (1) The strategy of commensality (eating together) successfully broke down psychological barriers and shifted interaction patterns from segregative to inclusive; (2) Problem tree analysis revealed that the root of the conflict was not ethnic sentiment, but a regulatory vacuum at the village level; (3) The establishment of the Sane Siri (One Heart) Forum, which integrates restorative customary sanctions into the village governance structure. This program concludes that a cultural approach placing the community as the subject of the solution is more effective in maintaining social cohesion in transmigration contact zones.